The Study of Plot Size in Forest Enumeration Surveys - Mokashi, V. K.; Yadav, Z. R. (Indian Forester, 1969)
The study of plot size to be employed in forest enumeration surveys has not received the attention it deserves. Investigations have been carried out to determine the relationship between plot size and variance empirically. The variance law empirically established by Jessen has been examined and is found to follow the same. Broad indications have been given in regard to plot size for various situations of costs of enumerations and movement from plot to plot.